A reinvenção da corporeidade: o cotejo entre a tradição moderna e a tradição indígena - Lima, Elias Lopes de (2009)
The objective of this research aims to precise how the notion of body contributes to a conception of space giving evidence to the intrinsic relation between these two categories of the human understanding and contribute to the reflection of the anachronism that rules the geographic thought concerning the dualism that contrasts an organic perspective and an inorganic vision. We collate thus the body according to distinct and conflicting rationalities that refers to the way diverse cultures apprehend notions of time and space; conceptions that disagree with many aspects in modern thought. Contrasting, therefore, different body conceptions that are not annulled by the presence of the other, but, principally, to enrich them in face of mutual recognition and, more precisely, to concern them as possibilities of reorientation of our presence in the world in face of a crisis of paradigms. From this point, we are able to contrast them in order to extract an always provisory synthesis to reaffirm the body as a point of inflection of the conditioned state promoted by the circuits of hegemonic power. It is in this direction that we discuss the reinvention of body notion.